2019
DOI: 10.1089/ten.teb.2018.0345
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction Strategies of the Ureter and Urinary Diversion Using Tissue Engineering Approaches

Abstract: Cartilage consists of chondrocytes and a special extracellular matrix (ECM) having unique biochemical, biophysical, and biomechanical properties that play a critical role in the proliferation and differentiation of cells inherent to cartilage functions. Cartilage tissue engineering (CTE) requires recreating these microenvironmental physicochemical conditions to lead to chondrocyte differentiation from stem cells. ECM-derived hybrid scaffolds based on chondroitin sulfate, hyaluronic acid, collagen, and cartilag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 202 publications
0
14
0
Order By: Relevance
“…End-to-end anastomosis is applied for patients presenting short-length ureteral deficit due to the successful outcomes of this technique[ 20 ]. For the long-segment reconstruction, the use of autologous bowel is the gold-standard[ 3 ]. However, this kind of tissue presents many potential complications, including metabolic imbalance, malabsorption of vitamins, cholelithiasis, nephrolithiasis and infections[ 21 ].…”
Section: Anatomy Pathologies and Current Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…End-to-end anastomosis is applied for patients presenting short-length ureteral deficit due to the successful outcomes of this technique[ 20 ]. For the long-segment reconstruction, the use of autologous bowel is the gold-standard[ 3 ]. However, this kind of tissue presents many potential complications, including metabolic imbalance, malabsorption of vitamins, cholelithiasis, nephrolithiasis and infections[ 21 ].…”
Section: Anatomy Pathologies and Current Treatmentsmentioning
confidence: 99%
“…However, this technique is limited by the characteristics of the donor, the secondary donor site injuries, and the adequacy of the function of the grafted tissue[ 2 ]. Indeed, it is easy to conceive that the intestinal bowel, used for ureteral reconstruction, cannot provide the required impermeability function[ 3 ] since the leading role of the intestinal bowel is to absorb nutrients, while the role of the ureters is the opposite, acting as a barrier to protect other tissues from urine. On the other hand, allogeneic transplantation is limited by the risk of tissue rejection and the availability of these tissues.…”
Section: Introductionmentioning
confidence: 99%
“…So-called scaffolds are the building blocks to promote tissue regeneration, which could be produced from decellularized native tissue. Scaffolds can be further categorized on the basis of whether they are directly implanted, seeded with cells prior to implantation, or preimplanted before functional implantation [57]. The smallintestinal submucosa (SIS), a heterologous, biocompatible, nonimmunogenic collagen matrix originating from the porcine intestinal submucosal layer, is a resorbable biological The SIS has been demonstrated to facilitate the successful regeneration of host tissues from bench to bedside, including those used for ureteral reconstruction the in preclinical studies (as shown in Table 3).…”
Section: Tissue Engineering and Regenerationmentioning
confidence: 99%
“…The complexity of surgery procedure, toxic effect of urine, and high level of minimum requirements for candidate constructs have hindered the advances in this area. Different strategies of preparation and application of tissue-engineered constructs for ureter tissue reconstruction have been studied so far (El-Hakim et al, 2005;Wolfe et al, 2011;Zhao et al, 2012Zhao et al, , 2016Salehipour et al, 2013;de Jonge P. K. et al, 2018;Janke et al, 2019). As urinary diversion tissue engineering holds relatively similar requirements and problems to the ureter, the reconstructive approaches are quite comparable.…”
Section: Ureter Tissue Engineeringmentioning
confidence: 99%